Kinetic Study of first Order Ion Exchange Reaction by the Application of Tracer Technique - Lokhande, R.S.; Gandhe, M.V. (Asian Journal of Chemistry, 2010)
Analysis of the kinetic study of first order in exchange reaction rate varying from 26 to 48ºC and also at different concentration of potassium iodide solution (0.005 M to 0.1 M) was carried but by the application of a tracer isotope131 I.The specific reaction rate for the change in temperatrue as well as the amount of resin was calculated. It was observed that as the temperature increases, i.e., from 26 to 48ºC at 0.005 M there is an increase in the specirfic reaction rate, but there is an pronounced increase when the amount of resin increases from 1g to 5g at 0.005 M at 26ºC. The energy of activation was also calculated for various temperatures at different concentrations. It was observed that there is decrease in the energy of activation as the concentration increases.